Teknik Pengerjaan Artefak Tulang di Situs Liang Bala Matti, Bontocani, Bone - Andi Muhammad Saiful Andi; Budianto Hakim (Tumotowa, 2022)
This research studies bone artefact at Liang Balang Matti Site that has occupied by Toalian. The goals of this research know technical working bone artefact and sequence priority manufacture bone tools that be used. The methods in this research are macro identification in surface of the artefact bone to know use-wear, sequence of working surface specimen, and working-trace and analysis with combining use-wear and working-trace. The result of the method explains that technical modifications of bone artefacts in this site are diverse of technical styles such as cut, scrapped, knapped, shaped, and ground. The prime priority of using bone artefact in this site is artefact with margin shaping and invasive shaping. Based on these remains, the conclusion of the research describes that method of working bone artefact by inhabitants of Balang Matti Site becomes distinguishing if compare with other Toalian cultures that inhabit cave sites in South Sulawesi.